Preoperative vaginal wash with povidone iodine solution to reduce post caesarean infectious morbidity - Zainab Jaber AI Budairi; Hameed Faisal Al-Zaidy; Mahdi Saleh Hadi (Zien Journals, 2023)
Post-operative infection is frequently seen in Caesarean section. Vaginal wash with 10% povidone iodine & Antibiotic prophylaxis may have significant impact in reduction of infections and thus the need to study their roles in sepsis prevention systematically.
Keywords: operative; frequently; Caesarean; prevention